The relative susceptibility of four cephalosporins to a beta-lactamase from Bacillus cereus - Russell, A. D. (1973)
The effects of purified beta-lactamase from Bacillus cereus on the activity of four cephalosporins are described. Drug inactivation was measured spectrophotometrically and confirmed by microbiological assay and by microbiological techniques involving determinations of minimum inhibitory concentrations and growth curves of Staphylococcus aureus NCTC 6571 (Oxford) in broth containing drug ± enzyme. Cephaloridine was the most sensitive of the four cephalosporins, followed by cephalothin and the sodium salt of 7-cyanacetamidocephalosporanic acid, with cephalexin considerably resistant to inactivation. The possible use of this beta-lactamase in the sterility testing of cephaloridine and cephalothin is examined.